Emerging Trends and Strategies in Indian Retailing - Malliswari, M. N. (Indian Journal of Marketing, 2007)
Retailing in India is slowly on the rise with changing consumer preferences and tastes and evolution of a global structure. Money is no longer a constraint. A gradual change in the retailing scenario is noticeable with regular shops making way to high end market malls and stores in urban areas. The cosmopolitan outlook projected by retail outlets with availability of almost everything under one roof makes retail outlets a star attraction for one and all. As Income levels increase radically resulting in higher disposable income, people continue to look for happiness in acquiring things albeit with greater vigor. Lifestyles are changing not only because of changing incomes but also because of the mind- boggling variety of goods that are now available for acquisition and consumption. Increased income is finding its way into the coffers of retailers who are able to offer more comfort, luxury and status to consumers. Providing consumer satisfaction has been replaced by providing consumer delight with marketers making indefatigable efforts to innovate not only in products, but also in the methods of marketing.